Black Phosphorus Quantum Dots Encapsulated Biodegradable Hollow Mesoporous MnO2: Dual‐Modality Cancer Imaging and Synergistic Chemo‐Phototherapy. (16th July 2021) - Wu, Yafeng; Chen, Zixuan; Yao, Zhipeng; Zhao, Kaige; Shao, Fengying; Su, Juan; Liu, Songqin
Abstract: To achieve an accurate diagnosis and efficient tumor treatment, developing a facile and powerful strategy to build multifunctional nanotheranostics is highly desirable. Benefiting from the distinct characteristics of black phosphorus quantum dots (BPQDs), herein, a versatile nanoprobe (H‐MnO2 /DOX/BPQDs) is constructed for dual‐modality cancer imaging and synergistic chemo‐phototherapy. The hollow mesoporous MnO2 (H‐MnO2 ) nanoparticles are sequentially decorated with a cationic polymer poly (allylamine hydrochloride) (PAH) and an anionic polymer poly (acrylic acid) (PAA). The obtained H‐MnO2 ‐PAH‐PAA is covalently grafted with BPQDs‐PEG‐NH2 via a carbodiimide cross‐linking reaction and then loaded with anti‐cancer drug DOX to form final nanoprobe H‐MnO2 /DOX/BPQDs. Under the tumor microenvironment, H‐MnO2 /DOX/BPQDs is degraded to release encapsulated functional molecules DOX and BPQDs. DOX acts as the chemotherapy and fluorescence imaging agent, and BPQDs endows the nanoprobe with photodynamic therapy (PDT) and photothermal therapy (PTT) abilities under dual laser irradiation of 630 and 808 nm. H‐MnO2 offers contrasts for magnetic resonance imaging (MRI) and facilitates conversion of endogenous H2 O2 to oxygen, thereby relieving tumor hypoxia and enhancing PDT efficacy. All in vitro and in vivo results demonstrate that the designed nanoprobe displays dual‐modality MRI/FL imaging and synergistic chemotherapy/PDT/PTT, which ultimately enhances the accuracy of cancer diagnosis and therapeutic performance. Abstract : A versatile nanoprobe (H‐MnO2 /DOX/BPQDs) is designed for dual‐modality cancer imaging (MR/FL) and synergistically enhanced chemo‐phototherapy with the modulation of the tumor microenvironment, which ultimately enhances the accuracy of cancer diagnosis and therapeutic performance.